2022
DOI: 10.56499/jppres22.1471_10.6.1026
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antioxidant properties and antimicrobial activity of the ethanolic extract of Senecio nutans Sch. Beep. (Asteraceae)

Abstract: Context: Senecio nutans Sch. Beep. is used by the Andean population of Ayacucho-Peru as traditional medicine for various health problems. Aims: To evaluate the antioxidant and antimicrobial activity of the ethanolic extract of leaves of S. nutans against the enteropathogen Escherichia coli and the filamentous fungus Aspergillus niger. Methods: The antioxidant capacity of the ethanolic extract was evaluated by ABTS, DPPH, and FRAP assays; the antimicrobial activity was evaluated by the agar diffusion method, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 28 publications
0
4
0
1
Order By: Relevance
“…Some investigations have shown that ethanolic extracts of S. nutans have antimicrobial and antibacterial activity [ 4 , 7 , 8 , 9 ]. These notable properties are associated with the different types of secondary metabolites present in the plant.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Some investigations have shown that ethanolic extracts of S. nutans have antimicrobial and antibacterial activity [ 4 , 7 , 8 , 9 ]. These notable properties are associated with the different types of secondary metabolites present in the plant.…”
Section: Introductionmentioning
confidence: 99%
“…These notable properties are associated with the different types of secondary metabolites present in the plant. Mainly, the Senecio species are rich in antioxidant compounds such as polyphenols (phenylpropanoids, 3,5-di-O-caffeoyl quinic acid, 3,4-di-O-caffeoyl quinic acid, chlorogenic acid methyl ester, caffeic acid and chlorogenic acid, tannins, and flavonoids) [ 7 , 10 ], terpenes [ 4 ], and p -hydroxyacetophenone derivates [ 11 , 12 , 13 ]. p -Hydroxyacetophenone derivates are the most abundant compounds in the aerial parts of S. nutans species [ 3 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…El tamizaje fitoquímico, la medición del contenido de componentes polifenólicos y el contenido mineral son estudios in vitro que evalúan el potencial medicinal de las plantas y permiten el descubrimiento e identificación de nuevas moléculas de relevancia farmacológica (Surco-Laos et al, 2022) . También ayuda a promover la conservación y protección de los ecosistemas, particularmente en áreas investigadas y rara vez perturbadas, como los afloramientos de granito (Mendoza et al, 2020).…”
Section: Introductionunclassified